The Role of Surgery in High-Grade Neuroendocrine Cancer: Indications for Clinical Practice - Petrella, Francesco; Bardoni, Claudia; Casiraghi, Monica; Spaggiari, Lorenzo (Frontiers in Medicine, 2022)
Pulmonary neuroendocrine tumors (pNET) represent a particular type of malignant lung cancers and can be divided into well-differentiated low-grade NET and poorly-differentiated high-grade NET. Typical and atypical carcinoids belong to the first group while large cell neuroendocrine carcinomas (LCNEC) and small-cell lung cancers (SCLC) belong to the second one. SCLC has the worst prognosis among all lung cancer neoplasms: in fact, the two-year survival rate is about 5% and median survival usually ranges between fifteen and twenty months. The surgical treatment of SCLC has thus infrequently been judged as a valuable aspect of the therapeutic approach, the gold standard treatment being a combination of platinum-based chemotherapy and radiotherapy. As LCNEC are rare, there is a lack of extensive literature and randomized clinical trials, therefore the curative approach is still controversial. Current treatment guidelines suggest treating LCNEC by surgical resection in non-metastatic stages and recommend adjuvant chemotherapy according to SCLC protocol . Upfront surgery is suggested in early stages (from I to IIB), a multimodality approach is recommended in locally advanced stages (III) while surgery is not recommended in stage IV LCNEC. The rate of surgical resection is quite low, particularly for SCLC, ranging from 1 to 6% in limited diseases; lobectomy with radical lymphadenectomy is considered the gold standard surgical procedure in the case of limited disease SCLC and resectable LCNEC; pneumonectomy, although reported as an effective tool, should be avoided in the light of local and distant recurrence rates.